DESIGNING CHATBOT FOR COLLEGE INFORMATION MANAGEMENT - Herry Derajad Wijaya; Wawan Gunawan; Reza Avrizal; Sutan M Arif (IJISCS (International Journal of Information System and Computer Science), 2020)
Information plays an important role in human daily life in which it is expected to be more understood, fast, clear and accurate. In line with technology development and the mission of Informatics study program to develop its services for college students, that is, information is derived through information systems and chat. Students in this case is whom study at the university, institution or academy. This study aims to create Chatbot as Virtual Assistant that provides information for college students through data stored on the system which contains Informatics study program and new information if the data is not founded. Chatbot is a computer program designed to socialize interactive conversations or communication to users (humans) through a text, sound and visual. Through this application, they are able to communicate for various pratical purposes such as customer service, information acquisition and a value of digital campus with integrated information system. Thus, Chatbot with artificial intelligence eases users to obtain information quickly and precisely.